Peningkatan Kompetensi Kerja Pejabat Pemeriksa Keselamatan Kapal Melalui Pendidikan dan Pelatihan Terhadap Keselamatan Pelayaran - Sonny, Imam; Ardhina, Dila; Thamrin, Muhammad; Pahala, Yosi; Sugiyanto, Sugiyanto (Institut Transportasi dan Logistik Trisakti, 2024)
Education and training is a job requirement to improve mastery of various skills, expertise and knowledge based on detailed and routine work activities. Shipping safety is needed to ensure the safety of shipping activities and the preservation of the environment, so the competence of Ship Safety Inspector Officers who have qualifications in the field of ship safety is required. This research uses a path analysis technique approach by testing linearity, normality and hypotheses. The aim of this research is to partially or simultaneously determine the direct and indirect influence of official work competency variables through education and training on shipping safety. The total sample was 60 respondents who were Marine Inspector Training participants who were currently taking part in training at the Maritime Transportation Education and Training Center. The findings of this research show that shipping safety is directly positively influenced by the variables of work competency and education and training, thus efforts can be made to increase shipping safety by increasing the work competency of Ship Safety Inspector officials and education and training